2003
DOI: 10.1177/15353702-0322807-11
|View full text |Cite
|
Sign up to set email alerts
|

Casein Binds to the Cell Membrane and Induces Intracellular Calcium Signals in the Enteroendocrine Cell: A Brief Communication

Abstract: Dietary protein but not amino acids stimulates cholecystokinin (CCK) secretion in rat mucosal cells. However, the dietary protein sensory mechanisms and the intracellular signal pathway in the enteroendocrine cells have not yet been clarified. The relationship between dietary protein binding to cell membrane and intracellular calcium responses were examined in the CCK-producing enteroendocrine cell line STC-1. The binding of solubilized STC-1 cell membrane to proteins was analyzed using a surface plasmon reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Recent reports have shown that a G-protein coupled receptor (GPCR), GPR93, mediated the peptone-induced CCK secretion in STC-1 cells, 26,27) and we have demonstrated the involvement of the Gq pathway for BconP-induced CCK secretion in these cells. [28][29][30] We have recently found the calcium-sensing receptor, CaR, to function as the receptor for the arginine-rich 51-63 peptide in -conglycinin by inducing intracellular Ca 2þ mobilization for triggering subsequent CCK secretion in EECs. 31) It is therefore possible that these GPCRs can also act as receptors for BconB peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that a G-protein coupled receptor (GPCR), GPR93, mediated the peptone-induced CCK secretion in STC-1 cells, 26,27) and we have demonstrated the involvement of the Gq pathway for BconP-induced CCK secretion in these cells. [28][29][30] We have recently found the calcium-sensing receptor, CaR, to function as the receptor for the arginine-rich 51-63 peptide in -conglycinin by inducing intracellular Ca 2þ mobilization for triggering subsequent CCK secretion in EECs. 31) It is therefore possible that these GPCRs can also act as receptors for BconB peptides.…”
Section: Discussionmentioning
confidence: 99%
“…59 It has been proposed that plasma membrane receptors exist in enteroendocrine cells for casein (in particular a-casein), which are responsible for caseininduced, L-type, calcium channel-mediated increases in intracellular calcium observed in an enteroendocrine cell line, STC-1. 60 Recently, nsLTPs have been demonstrated to bind to ubiquitous plasma membrane receptors in plant cells, and the authors speculated that there might be the possibility of similar interactions taking place with animal membranes that might be relevant to allergenic potential. 61 …”
Section: Membrane-bound Receptorsmentioning
confidence: 99%
“…First, we demonstrated binding of CSN1S1 on monocytic cells; however, this finding does not prove the presence of specific binding sites, because unspecific attachment may occur. Early experiments using bovine casein and human and animal leukocytes and other cell types suggested that casein binding receptors exist (13)(14)(15)47), but this finding cannot easily be transferred to human caseins because sequence homology is weak (31). For instance, the identity between the human CSN1S1 mRNA (accession code NM_001890; http://www.ncbi.nlm.nih.gov/Genbank) and the homologs of cattle (X00564), rat (NM_138874), and mouse (NM_007784) is 57.6, 49.8, and 47.8%, respectively (determined by the Euopean Molecular Biology Open Software Suite Align tool at the European Bioinformatics Institute, http://www.ebi.ac.uk).…”
Section: Discussionmentioning
confidence: 99%